1981
DOI: 10.1037/0022-3514.41.4.766
|View full text |Cite
|
Sign up to set email alerts
|

Machiavellianism and deception.

Abstract: Subjects who held a Machiavellian view of life, as measured by Christie's Mach Scales, were more convincing liars than non-Machiavellians. Sixty-four college students (high and low Mach men and women) were videotaped denying knowledge of a theft. Half had just been directly implicated in the theft; the other half made the same denial truthfully. A different group of 64 high and low Mach men and women college students viewed the 1.25-minute videotape clips in random sequence and judged the denials for veracity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
6

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 14 publications
2
60
0
6
Order By: Relevance
“…They might hide knowledge rationally due to organizational norm or the protection of other party's interest. According to Geis and Moon (1981), High Machiavellians are skilful liars, and lying high Machiavellians are more believed than lying low Machiavellians , while low Machiavellians tend to be more honest, upright, and pro-social [27]. Therefore, there might be no difference between high Machiavellianism and low Machiavellianism on rationalized hiding.…”
Section: Discussionmentioning
confidence: 96%
“…They might hide knowledge rationally due to organizational norm or the protection of other party's interest. According to Geis and Moon (1981), High Machiavellians are skilful liars, and lying high Machiavellians are more believed than lying low Machiavellians , while low Machiavellians tend to be more honest, upright, and pro-social [27]. Therefore, there might be no difference between high Machiavellianism and low Machiavellianism on rationalized hiding.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies found that some communicators were harder to detect when they lied than others (Bond, Kahler, & Paolicelli, 1985;DePaulo & Rosenthal, 1979;Geis & Moon, 1981;Kraut, 1978;Miller et al 1983;Riggio & Friedman, 1983;Sakai, 1981;Zuckerman, DeFrank, Hall, Lawrence, & Rosenthal, 1979). These researchers found that successful liars tend to be rated as more "honestlooking" (Bond et al 1985;Zuckerman et al 1979), score higher on the machiavellianism scale (DePaulo & Rosenthil, 1979;Geis & Moon, 1981), score higher on the self-monitoring scale (Miller et al 1983), and score higher on dominance, exhibition, and emotional sending skill (Riggio & Friedman, 1983).…”
Section: Humans As Deceiversmentioning
confidence: 99%
“…These researchers found that successful liars tend to be rated as more "honestlooking" (Bond et al 1985;Zuckerman et al 1979), score higher on the machiavellianism scale (DePaulo & Rosenthil, 1979;Geis & Moon, 1981), score higher on the self-monitoring scale (Miller et al 1983), and score higher on dominance, exhibition, and emotional sending skill (Riggio & Friedman, 1983).…”
Section: Humans As Deceiversmentioning
confidence: 99%
“…Hence, trait emotional intelligence which represents people's self-perceptions of their emotional abilities correlated negatively with Machiavellianism (Petrides et al, 2011;Ali et al, 2009;Austin et al, 2007). Higher Machiavellians tend to lie more and have an ability to easily convince the others (Exline et al, 1970;Geis and Moon, 1981). That is, higher Machiavellians use interpersonal strategies to support the use of deception, manipulation and exploitation (Ali, et al, 2009) to gain and to maintain power in interpersonal relationships (Vigoda-Gadot and Drory, 2006).…”
Section: The Role Of Agementioning
confidence: 99%